2016
DOI: 10.5565/rev/redes.591
|View full text |Cite
|
Sign up to set email alerts
|

Redes sociais e conflito organizacional

Abstract: As organizações são redes sociais cujos membros estabelecem entre si ligações de diversos tipos, formais e informais, positivas e negativas. O conflito entre atores é um processo comum que pode ser explicado com base num conjunto diverso de fatores. Contudo, o conflito interno às organizações tem sido pouco estudado, numa perpetiva de redes sociais. Para além disto, o conflito interorganizacional, analisado ao nível dos atores individuais, tem sido ainda menos estudado. No presente artigo, procuramos abordar o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(15 reference statements)
0
1
1
3
Order By: Relevance
“…Friendship bonds were spread among workers throughout the restaurant, as were strong cliques. Although the concentration of relationships in the same group may be common, as which occurred in the kitchen sector, friendship network connectivity between different groups is a positive factor that can reduce vulnerability in the face of possible conflicts and uncertainties (Lima et al, 2016). These data differ from previous research (Colares & Freitas, 2007;Santiago, 2012) which identified problems in relationships and communication in food producing units.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Friendship bonds were spread among workers throughout the restaurant, as were strong cliques. Although the concentration of relationships in the same group may be common, as which occurred in the kitchen sector, friendship network connectivity between different groups is a positive factor that can reduce vulnerability in the face of possible conflicts and uncertainties (Lima et al, 2016). These data differ from previous research (Colares & Freitas, 2007;Santiago, 2012) which identified problems in relationships and communication in food producing units.…”
Section: Discussioncontrasting
confidence: 60%
“…Also there are trust networks, which are similar to friendship networks, but involve bonds of loyalty and respect. Several researches have addressed these themes in the environment of organizations (Brennecke & Rank, 2016;Gonçalves, Lebarcky, & Muylder, 2015;Lima et al, 2016;Loiola & Lagemann, 2013;Macambira, Bastos, & Rossoni, 2015). Cross, Borgatti and Parker (2002) presented as a reference for research and intervention, five types of informal networks that are more focused on sharing information and knowledge: (1) communication network: communication network with continuous interactions on a particular theme, is important in mapping of subgroups; (2) information network: network with exchange of relevant information in carrying out the work; (3) Problem solving network: network with problem solving interactions (4) Knowledge network: a network that maps actors who are recognized for their knowledge and skills; (5) Access network: network with mapping of accessible actors to transfer knowledge in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Há também resistência do trabalhador em expor sua atividade, já que a informalidade pode ser associada à ilegalidade, diminuindo a concordância em participar de entrevistas. Com trabalhadores inseridos em organizações formais é possível ter acesso à lista completa de funcionários e usá-la em investigação sobre redes sociais, como feito em Lima, Maia, Menezes, e Santos (2016).…”
Section: Tipos De Redes Analisadas E Definição De Participantesunclassified
“…O tema redes interorganizacionais está presente em diversos estudos na medida que se verifica as organizações como redes sociais. Nelas observa-se que seus membros, estabelecem entre si ligações de diversos tipos, formais e informais, positivas e negativas, entre outras (Lima et al, 2016). Amato Neto (2000) evidencia a relevância da formação e do desenvolvimento de redes de empresas em países industrializados, como Itália, Japão, Alemanha e os chamados países emergentes, como México, Chile e Argentina.…”
Section: Redes Interorganizacionaisunclassified